The Settlement Pattern of Galo-Galo Island Fishermen In The Morotai Island District - Kapita, Hartati; Fahmi Aja, Muhammad (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Settlements of fishermen are usually inhabited by people whose main livelihood is dependent on the sea, and the building pattern is located on the coast or sea waters; a close relationship between the lives of fishermen and nature is shown by the settlement pattern located on the seashore. Fishermen's settlements are formed from similarities in culture and main livelihoods; other factors shape the character of a fisherman's settlement. This study aims to obtain the character of the fishermen's settlement pattern on the island of Galo-Galo both from the Settlement Pattern, Land Use Pattern, and Road Network Pattern so that it can be the direction and strategy for the sustainable development of fishermen's settlements, especially in communities located on small islands. Fishermen's houses and docks. The land condition of Galo-Galo village is sloping with craggy soil. Land use in Galo-Galo village tends to approach the coast of the fishermen's settlement pattern. Galo-Galo Village also includes other important places, such as landing places for fish catches and places for selling catches. Fish landing sites are usually located near the beach and are used to clean, process, and preserve fish caught by fishermen. Meanwhile, where the catch is sold, it is usually taken directly to the city.